Navigating Complexity in Design for Health Internships to Enhance Student’s Real-World Learning - Khoo, Cassandra; Reay, Stephen; Nakarada-Kordic, Ivana (Informa UK Limited, 2025)
In this paper, we reflect on two internship-based learning opportunities at a New Zealand-based university for design students to engage in authentic, real-world experiences in a design for health context. We present three hospital-based case studies as examples of the projects offered to students through Work Integrated Learning (WIL) internships and Summer Studentships (SS); a medication information leaflet, an information resource for women interrupting a pregnancy due to medical reasons, and a patient journey video and oral health resources for a children’s community dental service. Facilitating these real-world opportunities for design students has challenges, including building and maintaining connections and relationships with healthcare staff, careful selection of projects appropriate in scope and scale, managing and navigating expectations, and advocating for the value of design and implementation of students’ design solutions. Despite these challenges, both internships offer design students an opportunity to engage in the rich and complex healthcare context, while working on meaningful design projects that challenge them to consider the value and impact of their design practice. It highlights the benefits of engaging design students in different ways to better prepare them for an industry that asks designers to navigate tricky contexts and deliver design solutions to complex issues.
Keywords: 3303 Design; 4203 Health services and systems